Peptic Ulcer Disease : Can a Behavioral Factor be Implicated? - Andrey Dynyak (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
This article aims to highlight probable behavioral factors in the etiology of peptic ulcer (PUD). The working hypothesis is, due to an anatomic predisposition in the foregut blood supply and its gross anatomy, whenever a person with a replete or full stomach changes their position they may affect/disrupt blood supply to lower esophagus, stomach and proximal part of the duodenum. Our hypothesis states that if a person has habit of resting after meal, in reclined position, on either their right or left side, or is required to do so, due to prescribed bed rest, that the person will develop PUD, depending on their specific routine. Our hypothesis also proposes that different body positions are linked to different locations for the peptic ulcerative processes occurring. The proposed hypothesis has a number of implications. Firstly, PUD is somatic disorder and is a disease caused by lifestyle and systematically repeated habitual behaviors. As such, treatment should focus on the patient discussing their lifestyle habits, making them aware of their after-meal behavior and the link that the behavior has to PUD. Secondly, the primary therapeutic action should focus on postural behavioral therapy, adjusting habit-formed after-eating routines, that once remedied can reverse PUD.